Biofilm Composition Changes During Orthodontic Clear Aligners Compared to Multibracket Appliances: A Systematic Review - Alba Belanche Monterde; Javier Flores-Fraile; Esteban Pérez Pevida; Álvaro Zubizarreta-Macho (Microorganisms)
Clear aligner treatment seems to be a good option for the periodontal patient by the reason of being removable. Multibracket appliances are more difficult to mantain clean and some bacteria might prefer to adhere on the archwire. A systematic review was carried out using 4 electronic databases (Pubmed-Medline, Scopus, Cochrane and Web of Science). The selected trials included quantitative (Shannon index, Simpson index, relative abundances) and/or qualitative (alpha and beta diversity) analysis in patients using clear aligners and multibracket appliances. Initially, a total of 123 articles were found after selecting clinical trials. The inclusion and exclusion criteria were applied by two authors. Finally, 20 articles were selected for the systematic review. The results showed that clear aligner treatment produced less dysbiosis in the selected bacteria compared to multibracket appliances. However, some microbiological changes were observed in some articles during clear aligner use. Oral dysibiosis was related with intestinal dysbiosis, inflammatory response and even cancer. The Firmicutes/Bacteroidetes ratio showed to have a very important role in this development. Periodontitis is also a bacterial disease and clear aligners were recommended to periodontal risk patients. Clear aligner treatment obtained less supra and subgingival biofilm changes compared with multibracket appliances but some bacteria were altered during treatment.